Evaluation of the Perception of Students and Professors of the Private Dental School about Remote Teaching in the Covid-19 Pandemic - Xavier, Camila Paola da Costa (2022)
Introduction: The World Health Organization (WHO) warned of a "Public Health Emergency of International Concern" at the end of 2019. Due to Covid-19, preventive and limiting strategies had to be adhered to, such as isolation and social distancing. This new global public health problem has affected several areas, including education. Because of the above, the objective of this study was to evaluate the perception of professors and students of the School of Dentistry of a private university about teaching in a remote regime. Methodology: Two different questionnaires were made available to professors and students. The data were tabulated and a descriptive analysis was performed because of the perception of remote teaching. Results: One hundred and four students and 26 professors answered the questionnaires. 76% of students and 100% of professors responded that they agreed with the remote method during a pandemic. However, 74% of students and 61.5% of professors disagree with the implementation of a blended learning model in the future. 74% of students reported difficulty focusing during remote classes, despite 74% of students rated their professors' performance as good or excellent. 56.7% of professors and 60.6% of students agreed with the improvement of learning with the use of tools such as Google Forms® and Kahoot®. Conclusion: students and professors felt safe with the remote teaching regime during the pandemic. However, it is estimated that after the pandemic period, face-to-face teaching will be encouraged again. Keywords: Distance learning. Remote learning. Alternative learning techniques.